METHOD FOR RECOVERING LITHIUM, COBALT AND OTHER METAL - KUME SHOICHI (2012)
PROBLEM TO BE SOLVED: To provide a method for recovering lithium, cobalt and the other metal from a lithium ion battery.SOLUTION: In the method for separating and recovering each metal, for the purpose of separating each metal from ores containing lithium and lithium sources, products containing lithium such as the lithium battery, and lithium compounds, or from metals and products containing lithium and aluminum, silica, kalium, cesium, rubidium or the like, a temperature in a furnace is raised in a range of 220°C or higher to 3,600°C or lower, an atmospheric gas (H2+CO) in the furnace is set to 12.8% or higher, and remaining oxygen is set to 2.4% to 0.